2008
DOI: 10.1159/000129696
|View full text |Cite
|
Sign up to set email alerts
|

CSF/Serum Folate Gradient: Physiology and Determinants with Special Reference to Dementia

Abstract: Background: Folate depletion has been implicated as a risk factor for neurodegenerative disorders. We hypothesized that transport of folate to the cerebrospinal fluid (CSF) compartment could be involved in the pathophysiology of these disorders. Methods: The CSF/serum folate gradient (RCSF/S) was studied in 205 subjects with suspected cognitive disorder. Its relation to clinical and biochemical indices, including the integrity of the blood-CSF barrier, were characterized. Results: In subjects who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
5
18
0
1
Order By: Relevance
“…Another study (18) showed similar results, while a further one (9) observed higher folate serum levels than in our population and lower CSF levels. However, this last study did not use multi vitamin intake as an exclusion criteria.…”
Section: Discussionsupporting
confidence: 85%
“…Another study (18) showed similar results, while a further one (9) observed higher folate serum levels than in our population and lower CSF levels. However, this last study did not use multi vitamin intake as an exclusion criteria.…”
Section: Discussionsupporting
confidence: 85%
“…Decreased folate and increased Hcy levels were also associated with changes in brain structures detected by imaging [30,31]. According to previous works [24,32,33] reported in table 4, plasma Hcy was slightly increased in both AD and nAD patients compared to control subjects matched for age, but the difference did not reach significance, probably because the groups’ size was rather small in our study or because the controls were not healthy subjects.…”
Section: Discussionmentioning
confidence: 51%
“…Likewise, the hypothesis that Hcy was a risk factor has been suggested by the observation of increased concentrations in plasma or serum from patients with AD [18,21]. Some studies have been published showing that the concentration of CSF folate was lower in AD patients compared to subjects without dementia [22,23,24,25]. Similarly, CSF Hcy was assayed in some studies including patients with AD and control subjects [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…From 1996-98 onwards, the hyperhomocysteinemic aspect of VaD (and AD) has attracted attention [33][34][35][36] An increase in hs-CRP may probably per se cause increased plasma tPA concentrations [29]. In our study we have shown ( Table 1) that hs-CRP is significantly lower in AD Table 2 were adjusted for hs-CRP.…”
Section: Resultsmentioning
confidence: 55%